2011
DOI: 10.2174/092986611795446012
|View full text |Cite
|
Sign up to set email alerts
|

Induction of β-1,3-Glucanase in Seeds of Maize Defective-Kernel Mutant (827Kpro1)

Abstract: β-1,3-glucanases are found in organisms as diverse as plants, animals, bacteria and fungi. In plants, such enzymes are not only associated with defense mechanisms against pathogens, but also play critical roles in physiological and developmental processes. Here we identified a new β-1,3-glucanase in maize seeds, and named it ZmGlucA. Sequence analysis revealed that ZmGlucA belongs to the class A of β-1,3-glucanase, a class related to defense and physiological processes in plants. mRNA and protein assays showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Comparison between the ZmGns sequences amplified from cDNA and genomic DNA (using primer pairs G113, 5′‐TCATCGATCGATCGACGACCATG‐3′ and G114, 5′‐GGCCCTCAGAATTCTATCTCTTTTTATTCATC‐3′) showed that there is no intron in ZmGns . A new homology search of ZmGns was performed using the full‐length cDNA sequence, which showed that there are at least 10 DNA or EST sequences available in GenBank or MaizeGDB that showed various identities to our ZmGns , including a seed‐specific glucanase cDNA (HM641756, 98.3%) reported by Branco et al (), a genomic DNA clone GRMZM2G125032 (98.3%) from MaizeGDB, as well as several other cDNA or ESTs, such as BT038595 (97.2%), NM_0011112264 (62%), and DQ147109 (53%). Based on DNA sequence identities, GRMZM2G125032 appears to be the genomic clone of HM641756 and our ZmGns shares a higher homology with HM641756/GRMZM2G125032 (21 nucleotide differences at DNA level and three amino acid differences at protein level) than with BT038595/ACF83600 (34 nt differences at DNA level and seven amino acid differences at protein level).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparison between the ZmGns sequences amplified from cDNA and genomic DNA (using primer pairs G113, 5′‐TCATCGATCGATCGACGACCATG‐3′ and G114, 5′‐GGCCCTCAGAATTCTATCTCTTTTTATTCATC‐3′) showed that there is no intron in ZmGns . A new homology search of ZmGns was performed using the full‐length cDNA sequence, which showed that there are at least 10 DNA or EST sequences available in GenBank or MaizeGDB that showed various identities to our ZmGns , including a seed‐specific glucanase cDNA (HM641756, 98.3%) reported by Branco et al (), a genomic DNA clone GRMZM2G125032 (98.3%) from MaizeGDB, as well as several other cDNA or ESTs, such as BT038595 (97.2%), NM_0011112264 (62%), and DQ147109 (53%). Based on DNA sequence identities, GRMZM2G125032 appears to be the genomic clone of HM641756 and our ZmGns shares a higher homology with HM641756/GRMZM2G125032 (21 nucleotide differences at DNA level and three amino acid differences at protein level) than with BT038595/ACF83600 (34 nt differences at DNA level and seven amino acid differences at protein level).…”
Section: Resultsmentioning
confidence: 99%
“…Also, RNA blot and in situ hybridization revealed that the Arabidopsis BG4 gene was specifically expressed in the style and septum of the ovary (Delp and Palva ). A maize glucanase, which shares 99% homology with this ZmGns, was reported to be seed‐specifically expressed (Branco et al ). However, whether this gene was expressed in silk was not examined in the study by Branco et al ().…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chitinases can act on cell walls, and an antifungal effect with positive implications on the germination rate is usually described for these proteins. , However, a role in normal plant growth and development is also admitted since in Arabidopsis alterations in chitinase expression can lead to cell wall malformations and abnormal cell shapes . Although higher chitinase levels were also found in an endosperm development mutant, no correlation between chitinase content and endosperm texture was detected. , …”
Section: Discussionmentioning
confidence: 99%
“…β-1,3-glucanases are involved in various plant processes, such as overwintering, inflorescence lengthening, male gametophyte development, pollination, seed development and germination, fruit physiology, defence against biotic and abiotic stress, and nutrient uptake from heterotrophic organisms [ 6 , 7 , 8 ]. Specific extracellular β-1,3-glucanases bind to the surface of ice crystals, limiting their growth in the apoplast, thus providing cryoprotection [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%